HOSPITAL PERFORMANCE MEASUREMENT ANALYSIS ISLAM IBN SINA WITH BALANCED SCORECARD (BSc) - Yulitasari; Semiarty, Rima (Airlangga Development Journal, 2025)
Performance measurement is an important factor for companies in assessing success. Performance measurement usually only focuses on financial measures, resulting in company managers only being oriented towards short-term profits. The results of measuring performance indicators in each perspective, some have reached the target/standard and some have not. Of the 28 performance indicators measured, 13 indicators have reached the standard/standard (46%), while the other 15 indicators (56%) have not reached the standard/target. The results of performance measurement obtained can be the basis for determining strategic plans. Community satisfaction based on budget usage so that more appropriate strategic planning must be made by taking into account the four aspects of performance in a balanced manner.